2022
DOI: 10.18488/73.v10i3.3074
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Quality of Local Government Financial Statements in Indonesia: Coercive Pressure Dominates

Abstract: Many financial statements of the Indonesian local government are still of concern due to the lack of disclosure, and not complying with standards and government regulations. This fact was pointed out in the poor audit results on the local government financial statements released by the Indonesian Supreme Audit Board (SAB). Using the perspective of institutional isomorphism theory, this study aimed to examine various potential factors that affect the quality of Indonesian local government financial statements, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…According to Brigham and Daves (2003) financial distress happened before the firm faced bankruptcy or failure when the firm could not make the payment schedule or when cash flow estimates indicated that the firm would soon be unable to satisfy its obligations. Negative cash flow statements, falling margins and profits, revenue decreases, management stress, and employee turnover are all warning indications that a firm is in financial trouble (Muhammad, Mastuki, Darus, & Ghani, 2019;Muriithi, 2022;Munisamy et al, 2022;Arifin et al, 2022;Oner & Oner, 2022). Newton (1975) claimed that before declaring bankruptcy, an organisation would go through four stages of deterioration: incubation, cash scarcity, financial insolvency, and final insolvency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Brigham and Daves (2003) financial distress happened before the firm faced bankruptcy or failure when the firm could not make the payment schedule or when cash flow estimates indicated that the firm would soon be unable to satisfy its obligations. Negative cash flow statements, falling margins and profits, revenue decreases, management stress, and employee turnover are all warning indications that a firm is in financial trouble (Muhammad, Mastuki, Darus, & Ghani, 2019;Muriithi, 2022;Munisamy et al, 2022;Arifin et al, 2022;Oner & Oner, 2022). Newton (1975) claimed that before declaring bankruptcy, an organisation would go through four stages of deterioration: incubation, cash scarcity, financial insolvency, and final insolvency.…”
Section: Literature Reviewmentioning
confidence: 99%